Movement and subjective task load characteristics of match officials during the Men`s and Women`s Rugby League World Cup - Twist, C.; Johnson, E.; Elliott, D.; Highton, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Rugby league match officials (i.e., a referee and two touch judges) must position themselves relative to the players` actions during a match to make appropriate decisions that enable regulation of the players` behaviour by administering the laws of the game. Influence of the official's role during matches (i.e., referee vs. touch judge) on the physical and subjective task loads remains to be elucidated. Likewise, whether an official's load is influenced when controlling men's or women's competition requires investigation. Therefore, the aims of this study were to examine the influence of the match official's role and whether they were officiating male or female players on their movement and subjective task loads during international match play.